HEDGES IN THESIS ABSTRACTS OF GRADUATE STUDENTS OF SEMARANG STATE UNIVERSITY (Universitas Negeri Semarang, 2014)
This study is meant to describe the hedges used by the English, Mathematics, Science, Social and Education Management graduate students of State University of Semarang in writing their thesis abstracts, find out whether or not there is a difference in the use of hedges, and explain why they used hedges in the ways they do. It used a descriptive qualitative-quantitative approach and the data were taken from the thesis abstracts. The unit of analysis is lexical hedges analyzed based on the Salager-Meyer’s (1994) taxonomy as well as Hyland’ taxonomy (1998) and non-lexical hedges as suggested by Navratilova (2013). The results show that hedges both lexical and non-lexical hedges were used. There is a difference among these graduate students in using hedges. Those in English, Social and Education Management had the tendency to use more hedges than those in Mathematics and Science. This tendency of using more hedges by those in English might be influenced by their cultures. Meanwhile, the preferences of those in Social and Education Management in using more hedges are possibly caused by its nature in which these two programs are categorized as ‘soft sciences’ that are surely not very numerical.